AuN films - Structure and chemical binding (2015)
AuN films were produced on 304 stainless steel using an arc-pulsed - assisted plasma physical vapor deposition system. The deposition was performed using an Au target in a nitrogen atmosphere at different pressures. The films were characterized using x-ray photoelectron spectroscopy and x-ray diffraction. A 398.1-eV binding energy was observed and assigned to gold nitride species. The x-ray diffraction patterns displayed a crystallographic structure that corresponded to the Au-fcc phase with broad diffraction lines. The observed widening of the Bragg diffraction lines (rocking curves) can be attributed to the presence of interstitial nitrogen atoms in the Au-fcc structure. © 2015 John Wiley & Sons, Ltd.